A phase I study afatinib/carboplatin/paclitaxel induction chemotherapy followed by standard chemoradiation in HPV-negative or high-risk HPV-positive locally advanced stage III/IVa/IVb head and neck squamous cell carcinoma. (February 2016) - Chung, Christine H.; Rudek, Michelle A.; Kang, Hyunseok; Marur, Shanthi; John, Pritish; Tsottles, Nancy; Bonerigo, Sarah; Veasey, Andy; Kiess, Ana; Quon, Harry; Cmelak, Anthony; Murphy, Barbara A.; et al.
Highlights: Maximum tolerated dose of afatinib with carboplatin/paclitaxel is 20 mg daily. Afatinib at doses >20 mg with carboplatin/paclitaxel should be used with caution. Afatinib needs further evaluation in management of newly diagnosed HNSCC. Summary: Introduction: Afatinib is an ErbB family receptor inhibitor with efficacy in head and neck squamous cell carcinoma (HNSCC). A phase I trial was conducted to determine the maximally tolerated dose (MTD) of afatinib in combination with carboplatin and paclitaxel as induction chemotherapy (IC). Material and methods: Patients with newly diagnosed, locally advanced HPV-negative or HPV-positive HNSCC with a significant smoking history were enrolled. Afatinib alone was given daily for two weeks as lead-in and subsequently given with carboplatin AUC 6 mg/ml min and paclitaxel 175 mg/m 2 every 21 days as IC. Afatinib was started at a dose of 20 mg daily and dose escalated using a modified Fibonacci design. After completion of IC, afatinib was discontinued and patients received concurrent cisplatin 40 mg/m 2 weekly and standard radiation. Toxicity was assessed using CTCAE version 4.0. Results: Seven of nine patients completed afatinib lead-in and IC. Five patients had partial response and two patients had stable disease after IC. Dose level 1 (afatinib 20 mg) was well tolerated with one grade 3 (ALT elevation) and one grade 4 (neutropenia) toxicities. However, dose level 2 (afatinib 30 mg) was not well tolerated with nine grade 3 (pneumonia, abdominal pain, diarrhea, pancytopenia, and UTI), two grade 4 (sepsis) and one grade 5 (death) toxicities. Conclusions: The MTD of afatinib given with carboplatin AUC 6 mg/ml min and paclitaxel 175 mg/m 2 is 20 mg daily. Combination of afatinib at doses higher than 20 mg with carboplatin and paclitaxel should be administered with caution due to the toxicities.